Resentment, Hate, and Hope in Amyotrophic Lateral Sclerosis - Oster, Craig; Pagnini, Francesco (Frontiers in Psychology, 2012)
Amyotrophic lateral sclerosis (ALS) is a fatal and progressive neurodegenerative disease. Despite much research having been conducted about psychological issues involved in living with ALS, anger and resentment have yet to be investigated. Moreover, the construct of “hope” has received little attention, so far. An online survey was created to investigate hate, resentment and hope issues in people with ALS, in relation to the willingness to adopt a strict nutrient dense diet if it were shown to increase longevity. Results indicate that there is a high level of hope in the sample. People who have lived with ALS for more time expressed a higher level of hope to live 10 years or more. Those who are married were more likely to have hope of living 10 years or longer and more likely to have lower levels of hate against ALS. Dietary self-care choices appear to be related to hope issues. Resentment and hate tended to be higher in people who have had ALS for less time, and in women. Despite some methodological limitations, the results suggest that hope, hate and resentment could be important issues to explore in future studies.